Pharmacokinetics and Pharmacological Properties of Chloroquine and Hydroxychloroquine in the Context of COVID‐19 Infection. Issue 6 (1st September 2020) - Nicol, Melanie R.; Joshi, Abhay; Rizk, Matthew L.; Sabato, Philip E.; Savic, Radojka M.; Wesche, David; Zheng, Jenny H.; Cook, Jack
Abstract : Chloroquine and hydroxychloroquine are quinoline derivatives used to treat malaria. To date, these medications are not approved for the treatment of viral infections, and there are no well‐controlled, prospective, randomized clinical studies or evidence to support their use in patients with coronavirus disease 2019 (COVID‐19). Nevertheless, chloroquine and hydroxychloroquine are being studied alone or in combination with other agents to assess their effectiveness in the treatment or prophylaxis for COVID‐19. The effective use of any medication involves an understanding of its pharmacokinetics, safety, and mechanism of action. This work provides basic clinical pharmacology information relevant for planning and initiating COVID‐19 clinical studies with chloroquine or hydroxychloroquine, summarizes safety data from healthy volunteer studies, and summarizes safety data from phase II and phase II/III clinical studies in patients with uncomplicated malaria, including a phase II/III study in pediatric patients following administration of azithromycin and chloroquine in combination. In addition, this work presents data describing the proposed mechanisms of action against the severe acute respiratory distress syndrome coronavirus–2 and summarizes clinical efficacy to date.